"Fontainebleau rock art" (Ile-de-France, France), an exceptional rock art group dated to the Mesolithic? Critical return on the lithic material discovered in three decorated rock shelters. (June 2017) - Guéret, Colas; Bénard, Alain
Abstract: Since the 19th century, the so-called "Fontainebleau rock art" have been recognized in small cavities of the southern part of the Ile de France, in a rare context typified by accumulations of eroded sandstone boulders. The dating of this non-figurative art, characterized by numerous grooved lines and grids, has always been the subject of much speculation. In the last thirty years, an attribution to the Mesolithic has been the most widely accepted interpretation owing to the discovery of highly worn lithic objects, considered as engraving tools and associated with Mesolithic artifacts in several rock shelters. This paper aims to question the Mesolithic hypothesis in the light of a new methodological and archaeological approach. First, a use-wear analysis of several hundred worn tools from three rock shelters confirms their connection with the numerous lines grooved in the sandstone walls. In a second time, a critical review of the archaeological data consolidates the Mesolithic dating. The engraving tools are always associated with a diagnostic industry, but the typology of the microliths discovered in the archaeological layers indicates mixture between several phases of the regional Mesolithic. Luckily, the typo-technological analyses of the engraving tool blanks highlight the systematic re-use of Early Mesolithic tools and bladelets as opposed to Late Mesolithic artifacts which are never worn by sandstone grooving. Considering the recurrence of these observations for the three studied rock shelters, the Early Mesolithic dating of the Fontainebleau rock art can be considered as a solid hypothesis, identifying the southern part of Ile-de-France as one of the major regions in Europe as concerns Mesolithic rock art. Highlights: A new archaeological study to confirm the Mesolithic dating of the Art of Fontainebleau A use-wear analysis to check the relation of worn lithic tools with rock art A critical review of archaeological contexts where worn tools have been found A typo-technological analysis of worn tools blanks to precise the dating An intensive rock art practice during the Early Mesolithic in Paris Basin